Analisis Kandungan Karbohidrat, Serat Dan Indeks Glikemik Pada Hasil Olahan Beras Siam Unus Sebagai Alternatif Makanan Selingan Penderita Diabetes Mellitus - Nany Suryani; Rijanti Abdurrachim; Nor Alindah (HB PRESS, 2016)
Rice is the staple food for the majority of the Indonesian people. Siam unus rice is a local rice in South borneo which has a low glycemic index is 50.1. Food with a low glycemic index, low in carbohydrates and high in fiber can help people with diabetes to control blood glucose levels. The purpose of this study is to analyze different of carbohydrate, crude fiber and the glycemic index in the processed siam unus rice (lemper nasi, arem-arem and pepes nasi) as altternatif snack diabetes mellitus. This research is experimental. Analysis of the carbohydrate content using the gravimetric method, crude fiber using Luft schoorl, while the glycemic index levels made by examining blood glucose levels to 8 healthy respondents. Blood glucose tests performed before feeding trials and for two hours afterward with a span of 30 minutes. The results of this study found no difference in carbohydrate content lemper nasi, arem-arem and pepes nasi (p = 0.040), there are differences in crude fiber lemper nasi, arem-arem and pepes nasi (p = 0.006), and no differences in glycemic index processed siam unus rice (p = 0.958). Glycemic index of lemper nasi and pepes nasi relatively low at 53.40 and 52.87, while arem-arem had moderate glycemic index that is equal to 55.34. Lemper nasi, arem-arem and pepes nasi can be used as an alternative snack with diabetes mellitus. Keywords : Carbohydrate Content and Fiber, Glycemic Index, Diabetes Mellitus, Siam Unus Rice